2007
DOI: 10.1103/physrevlett.98.113002
|View full text |Cite
|
Sign up to set email alerts
|

Antiproton Confinement in a Penning-Ioffe Trap for Antihydrogen

Abstract: Antiprotons (p[over]) remain confined in a Penning trap, in sufficient numbers to form antihydrogen (H[over ) atoms via charge exchange, when the radial field of a quadrupole Ioffe trap is added. This first demonstration with p[over] suggests that quadrupole Ioffe traps can be superimposed upon p[over] and e(+) traps to attempt the capture of H[over] atoms as they form, contrary to conclusions of previous analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…The proposed design of our apparatus is modular and readily allows, in a future stage, the insertion of a magnetic trap for H, which will be spatially separated from the region where the anti-atoms are produced. The spatial separation between the production and measurement regions, which is already a feature of the setup that we have presented here, differs significantly from the approach chosen by the other H experiments ATRAP [34] and ALPHA [35], which incorporate a trap that simultaneously confines charged and neutral particles. The experience gained in the first phase of AEGIS with the formation of an H beam will be used to optimize the design of a trapping system.…”
Section: Discussionmentioning
confidence: 97%
“…The proposed design of our apparatus is modular and readily allows, in a future stage, the insertion of a magnetic trap for H, which will be spatially separated from the region where the anti-atoms are produced. The spatial separation between the production and measurement regions, which is already a feature of the setup that we have presented here, differs significantly from the approach chosen by the other H experiments ATRAP [34] and ALPHA [35], which incorporate a trap that simultaneously confines charged and neutral particles. The experience gained in the first phase of AEGIS with the formation of an H beam will be used to optimize the design of a trapping system.…”
Section: Discussionmentioning
confidence: 97%
“…To trap both charged and neutral species simultaneously, the Minimum-B and Penning-Malmberg traps must be colocated. The compatibility of Minimum-B and PenningMalmberg traps remains controversial [4,5,7], but it is clear that the two are most compatible if the p's and e + 's are held close to the trap axis where the perturbations from the Minimum-B trapping fields are smallest [8,9,10]. Furthermore, holding the p's and e + 's near the axis increases their overlap, and slows the E × B drifts of the p's.…”
mentioning
confidence: 99%
“…The demonstrations disproved claims by some in the competing ALPHA collaboration that it was "impossible" to form H within the fields of a quadrupole Ioffe trap [26]. We first demonstrated that p could be stored in a nested Penning trap long enough to form H within a quadrupole Ioffe trap [24]. We next demonstrated that H atoms can indeed be formed within the fields of a Penning-Ioffe trap [25].…”
Section: Results From the Most Recent Grant Periodmentioning
confidence: 69%
“…The first two ATRAP accomplishments of the current grant period were demonstrations that H could be produced within the fields of a Penning-Ioffe trap [24,25]. The demonstrations disproved claims by some in the competing ALPHA collaboration that it was "impossible" to form H within the fields of a quadrupole Ioffe trap [26].…”
Section: Results From the Most Recent Grant Periodmentioning
confidence: 99%